Indicators for socio-religious harmony index (SRHI) instrument for Malaysia: findings of FDM expert panel - Ahmad Yusoff, Atifah; Abdullah, Muhammad Ridhuan Tony Lim; Endut, Mohd Nuri Al-Amin; Abdul Aziz, Enizahura; Talib, Ahmad Tarmizi (Universiti Putra Malaysia Press, 2018)
This study contributes to an understanding of the Malaysian socio-religious situation. Being a multi-religious country, Malaysia is not immune to contentious issues and incidents that challenge the relationship between different religious groups. Thus, it is crucial for the country to be conscious of its level of inter-religious relationship in order to maintain peaceful coexistence within the nation. This literature review is presented as a guideline to propose suitable indicators for the Socio-Religious Harmony Index (SRHI) instrument. This study uses the Design and Developmental Research (DDR) approach to conduct a Needs Analysis (Phase 1), development of the SRHI instrument (Phase 2) and evaluation of the index (Phase 3). This paper discusses Phase 2 of DDR, which is the development of the SRHI instrument. The method of this phase uses the Fuzzy Delphi Method (FDM) involving 14 expert panels invited to participate in the development of the instrument through a workshop. There were two rounds of FDM sessions, where the first round was to determine the indicators and the second round was to determine the sub-indicators. The end output of this paper is to present the findings of selected indicators for this index instrument as it was determined in FDM round one and two. The result shows that all 22 proposed indicators were accepted for inclusion in the SRHI instrument with the highest ranking indicators being mutual respect and the lowest ranking indicator being acknowledgement. The result of FDM round two shows that 53 sub-indicators were accepted out of 58 sub-indicators. Lastly, this paper presents the overall indicators and respective sub-indicators for the SRHI instrument.